(untitled) (Cardiovascular Journal, 2019)
Background: Primary percutaneous coronary intervention (PPCI) has been performed traditionally by using femoral approach. Transradial approach has become increasingly popular as it is likely to be less complicating, more comfortable and relatively cost effective having mortality and morbidity benefits. The aim of the study was to compare the in-hospital outcomes of transradial PPCI with that of transfemoral route. Methods: A total of 80 patients with ST elevation myocardial infarction (STEMI) who underwent PPCI were enrolled in the study. Patients were divided in two groups. Group-I: transradial PPCI; and Group-II: transfemoral PPCI. All patients were followed up during the period of hospital stay and adverse outcomes were observed and compared between the groups. Results: The result showed that bleeding took place in 2.5% patient of Group-I and 15% patients of Group- II. Vascular complications occurred in 2.5% and 12.5% patients of Group-I and Group-II, respectively. In Group-II, 7.5% patients died with none in Group-I. In Group-II, 37.5% patients experienced some sort of adverse outcomes whereas only 15% of the patients of Group-I did have such experiences (p<0.05). Bleeding and vascular complications were significantly more in Group-II (p<0.05). The mean hospital stay time was significantly lower in Group-I (p<0.001). Conclusions: Transradial PPCI is safer than transfemoral approach in respect of procedural and post procedural complications including bleeding, vascular complications and mortality. So, transradial approach may be an attractive alternative to conventional transfemoral approach and can be practiced routinely for PPCI. Cardiovasc. j. 2019; 11(2): 98-104